210 Nursing Home Residents in Acute Hospital – a Targeted ANPc Program to Improve Care. (16th September 2019) - Noonan, Claire; Ryan, Dan; Coughlan, Tara; Kennelly, Séan
Abstract: Background: NHR are the frailest group of older people and require a gerontologically attuned approach to combat multiple challenges presented to the practitioner. The in-reach ANPc liaison service aims to confront such challenges, by providing comprehensive gerontological input to all nursing home residents admitted to hospital under all specialities medical, geriatric, and surgical. Methods: This service commenced in September of 2018, working 9-5 Monday to Friday with limited leave cross-cover. All nursing home residents are reviewed by a Gerontology Advanced Nurse Practitioner candidate. Each patient received comprehensive geriatric assessment (CGA) with recommendations for care. All had follow up 2 weeks after discharge in telephone review clinic. Results: 118 nursing home residents were admitted for acute care in the study period; 96/118 (82%) were reviewed by the ANPc. 16/118 (14%) were discharged prior to review and 6/118 (5%) died within 24 hours of admission. All other patients were reviewed within 72 hours. All assessed residents had >1 recommendation for intervention to enhance care following CGA: Interventions included 31% (30/96) undiagnosed delirium identified and management advice given. 21% (20/96) had recurrent falls work up and advice. 27% (26/96) had recommendations and changes to admission medications. 37% (36/96) referrals to other HSCP therapy disciplines for complete holistic care. 11% (11/ 96) had advanced care planning regarding future illnesses. 13% (13/96) had palliative care advice and referral to community palliative care. Follow up telephone review clinics have further resulted in reduced readmission rates through liaison with NH staff post-discharge. Conclusion: The high complexity of this cohort of patients requires a timely, comprehensive gerontological approach in order to provide holistic care. They require a clearly defined approach to enhance care and minimise the need for unnecessary hospitalisations.